Analisis Pelaksanan Layanan Bimbingan Belajar Kelompok dalam Meningkatkan Motivasi Belajar Anak-anak di Desa Jaharun B Dusun 6 - Putri Herayati Manalu; Adelina Harahap; Haikal Dipo Nugraha; Ditya Paramitha; Khoirunniswa Az-Zihra T (MODELING: Jurnal Program Studi PGMI, 2023)
Tutoring services are a process of assistance services from mentors to mentoring participants in solving difficulties related to learning problems both at school and outside school so that tutors can adjust to their learning situations, can develop their learning skills, and form study habits with systematic and consistent and can achieve the maximum possible achievement. This research uses descriptive qualitative methods with data collection techniques carried out by observation and observation to test the level of children's learning motivation that affects children's understanding which was carried out on July 20, 2022 - August 15, 2022 in the village of Jaharun B Hamlet 6 Galang sub-district. The form of tutoring services provided to students is a guidance service that is tailored to the learning problems faced by students. By looking at the specifications of the problems faced by students, the supervising teacher can formulate a tutoring service program for students.